Математическое моделирование и численный анализ методом R-функций задач обтекания тел вязкой несжимаемой жидкостью - Ламтюгова, С. Н. (My University, 2016)
Дисертація присвячена розробці методів математичного моделювання і чисельного аналізу обтікання циліндричних тіл і тіл обертання в’язкою нестисливою рідиною на основі методу R-функцій. Для математичного моделювання стаціонарного повільного обтікання тіл (лінійні задачі) запропоновано новий чисельний метод, заснований на сумісному використанні методів R-функцій і Бубнова-Гальоркіна. Алгоритм розробленого метода не змінюється при зміні геометрії області, а структура розв’язку точно враховує як крайові умови на межі тіла, так і умову на нескінченності. Для математичного моделювання стаціонарного обтікання тіл (нелінійні задачі) отримав подальший розвиток чисельний метод, заснований на сумісному використанні методів R-функцій, послідовних наближень і Бубнова-Гальоркіна. Крім того, запропоновано використання нелінійного методу Гальоркіна для апроксимації невизначених компонент структури у разі розбіжності ітераційного процесу. Для розрахунку масообміну тіл з рівномірним поступальним потоком вперше розроблено чисельний метод, заснований на апрок- симації невизначених компонент у структурі розв’язку крайових задач методом Бубнова- Гальоркіна. Запропоновані чисельні методи проілюстровані обчислювальними експериментами. The thesis is devoted to the development of methods of mathematical modeling and numerical analysis of flow around cylindrical bodies and bodies of revolution by viscous incompressible fluid on the basis of the R-functions method. For the mathematical model22 ing of steady slow flow past bodies (linear problems), a new numerical method, based on the joint use of the R-functions and Bubnov-Galerkin method, has been suggested. The algorithm of developed method does not change with change in the area geometry; in addition, the structure of the solution accurately takes into account the boundary conditions at the boundary of the streamlined body and the condition at infinity. For the mathematical modeling of steady flow past bodies (nonlinear problems), a method, based on the combined use of the Rfunctions, the successive approximations and the Bubnov-Galerkin method, was further developed. Besides, a numerical method, based on the use of nonlinear Galerkin method for approximation of undefined components in the structure in case if iterative process diverges, has been suggested. For the calculation of mass transfer of bodies with uniform translation flow, a numerical method, based on the approximation of undefined components in the structure of the solution of boundary value problems by the Bubnov-Galerkin method, has been developed for the first time. The proposed numerical methods are illustrated by computational experiments.
Keywords: в’язка рідина; задача обтікання; рівняння Стокса; рівняння Озеєна; рівняння Нав’є-Стокса; функція течії; метод R-функцій; метод послідовних наближень; метод Бубнова-Гальоркіна; математичне моделювання; viscous fluid; flow past bodies; Stokes equation; Oseen equation; Navier- Stokes equations; stream function; R-functions method; successive approximations method; Bubnov-Galerkin method; mathematical modeling